Disclosure, use and interpretation of the financial information of governments: three essays - Columbano, Claudio (IE University, 2021)
This dissertation offers three studies aimed at shedding new light on the disclosure, use and interpretation of the financial information released by governments. The first two chapters are based on a hand-collected data set covering the forecasts disclosed by European Union governments over the period 2001-2018. The third chapter is based on 27 interviews with sovereign rating personnel working at four credit rating agencies and on archival material. Thechapters contribute novel perspectives on the peculiar financing reporting problem that confronts governments. In particular, the first chapter shows that the transparency of governmental financial disclosures responds to a cost-benefit trade-off similar to that which characterizes corporations. Accordingly, governments’ disclosure choices are self-interested, but they are not always driven by opportunistic motives. The second chapter reveals that equity investorsare active users of government forecasts, although they interpret them heterogeneously. In particular, the credibility of government’s commitment appears to explain the emergence of differential interpretations among investors when governments issue optimistic forecasts. The third chapter documents that credit rating analysts, too, differ in their interpretation of the financial information released by governments and use their subjective judgment to make up for the short comings of automated valuation models. Collectively, the dissertation extends extant accounting research by providing new perspectives on theunderstudied financial reporting problem that characterizes governments.
Divulgación, utilización e interpretación de la información financiera de los gobiernos: tres ensayos.
Esta tesis doctoral ofrece tres estudios destinados a arrojar nueva luz sobre la divulgación, utilización e interpretación de la información financiera publicada por los gobiernos. Los dos primeros capítulos se basan en un conjunto de datos recogidos por el autor que abarcan las previsiones divulgadas por los gobiernos de la Unión Europea durante el período 2001-2018. El tercer capítulo se basa en 27 entrevistas con analistas de calificación soberana que trabajan en cuatro agencias de calificación crediticia y en material de archivo. Los capítulos aportan perspectivas novedosas sobre el peculiar problema de la presentación de informes financieros que afrontan los gobiernos. En particular, el primer capítulo muestra que la transparencia de la información financiera de los gobiernos responde a una compensación de costes y beneficios similar a la que caracteriza a las empresas. En consecuencia, las decisiones de los gobiernos en materia de divulgación de información responden a intereses propios, pero no siempre están impulsadas por motivos oportunistas. El segundo capítulo revela que los inversores en capital social son usuarios activos de las previsiones gubernamentales, aunque las interpretan de manera heterogénea. En particular, la credibilidad del compromiso del gobierno parece explicar la aparición de interpretaciones diferenciales entre los inversores cuando los gobiernos emiten previsiones optimistas. En el tercer capítulo se documenta que los analistas de calificación crediticia también difieren en su interpretación de la información financiera publicada por los gobiernos y utilizan su juicio subjetivo para compensar las deficiencias de los modelos de valoración automatizados. En conjunto, la tesis amplía la investigación contable existente al proporcionar nuevas perspectivas sobre el problema de la información financiera que caracteriza a los gobiernos.
Keywords: Accounting; Contabilidad; Government; Gobierno; Financial information; Valuation; Información financiera; Valoración; Sovereign ratings; Calificación soberana; Credit rating agencies; Agencias de rating creditíceo